Analysis of Human Development Index of 13 Districts in West Kalimantan - Sulistianingsih, E; Junian, R; Wirarizki, S (KnE Social Sciences, 2018)
Human Development Index (HDI) is an indicator that becomes a prominent aspect reflecting the achievement of income, education, and health of community in a region. West Kalimantan, one of the provinces in Indonesia, is ranked 29 out of 34 provinces in terms of HDI. In addition, HDI of the province is the worst one among other five provinces in Kalimantan. For that reason, it is crucial to conduct research on influential factors that affect West Kalimantan’s HDI. There are three factors projected to give impact to HDI in this research. Those factors are Labor Force of Participation Rate (LFPR), Population Density (PD), and Poverty Level (PL). Data of the three factors from 13 districts in the province will be analyzed by panel regression and biplot. Panel regression used in this research assumes that there is no time-specific effect, slope coefficients are constant, and the intercepts vary across individuals. According to the result of analysis, it can be summarized that the fixed effect with adjusted determination-coefficient of 0.69 is the best model to analyze this case, where the three factors are statistically significant to HDI of the districts. After getting variables influencing HDI, biplot analysis with alpha 0 was conducted to the data. The latter analysis concluded that there was a strong and positive correlation between PL and LFPR. Moreover, the biplot analysis summarized that Sambas, Bengkayang, Mempawah, Sanggau, Sintang, Kapuas Hulu, Sekadau, and Melawi have a bigger number of LFPR rather than the other districts. Keywords: longitudinal, descriptive, singular-value-decomposition